Quality of care of patients with type 2 diabetes mellitus at a public sector district hospital - Kelly J. Fredericks; Mergan Naidoo (South African Family Practice, 2023)
Background: Globally, diabetes mellitus (DM) remains one of the leading causes of mortality, with approximately 2 million deaths in 2019, the condition also contributes significantly to adverse health conditions and costs. The study aimed to describe the quality of care (QOC) rendered to patients with type 2 DM (T2DM) seeking care at Wentworth Hospital (WWH), a district hospital in KwaZulu-Natal province, South Africa.